2018
DOI: 10.1108/bfj-07-2017-0372
|View full text |Cite
|
Sign up to set email alerts
|

Household acquisition of healthy food away from home

Abstract: Purpose The purpose of this paper is to analyze households’ acquisition of healthy food away from home (FAFH) from restaurants. Specifically, determinants of households’ decision to purchase healthy FAFH, the share of households’ FAFH expenditures allocated to healthy FAFH and the share of households’ FAFH calories obtained from healthy items are identified. Design/methodology/approach Using data from the National Household Food Acquisition and Purchase Survey, the UK Food Standards Agency’s Nutrient Profili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…On the other hand, the younger generations of consumers (Generation Y and Generation Z) prefer not only fruit and vegetables, but also other healthy food categories, such as fruit and vegetable juices or Various studies indicated that consumers perceive healthy food based on different factors including extrinsic attributes (product category, color and shape of packaging, product origin and label information) and intrinsic features such as sensory properties (taste, smell and consistency). In addition, one of the factors can be associated health benefits with individual food products (Motoki et al, 2021;Plasek and Temesi, 2019;Leschewski et al, 2018). Furthermore, our results identified five latent components determining the purchase and subsequently consumption of healthy foods, namely price-marketing factor, information and composition factor, authenticity factor, quality factor, as well as factor of motivation and support for the purchase and consumption of healthy foods.…”
Section: Attitudes Toward Healthymentioning
confidence: 67%
See 1 more Smart Citation
“…On the other hand, the younger generations of consumers (Generation Y and Generation Z) prefer not only fruit and vegetables, but also other healthy food categories, such as fruit and vegetable juices or Various studies indicated that consumers perceive healthy food based on different factors including extrinsic attributes (product category, color and shape of packaging, product origin and label information) and intrinsic features such as sensory properties (taste, smell and consistency). In addition, one of the factors can be associated health benefits with individual food products (Motoki et al, 2021;Plasek and Temesi, 2019;Leschewski et al, 2018). Furthermore, our results identified five latent components determining the purchase and subsequently consumption of healthy foods, namely price-marketing factor, information and composition factor, authenticity factor, quality factor, as well as factor of motivation and support for the purchase and consumption of healthy foods.…”
Section: Attitudes Toward Healthymentioning
confidence: 67%
“…In addition, one of the factors can be associated health benefits with individual food products (Motoki et al. , 2021; Plasek and Temesi, 2019; Leschewski et al. , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In reality, parents may have selected a fast food meal for other reasons (e.g. cost, Leschewski et al , 2018; nutrition knowledge, Choi and Zhao, 2014; efficiency, proximity, taste preference) – and given the increase in healthful options at these restaurants (Batada and Wootan, 2013), perhaps even nutrition and health.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this research focusses only on grocery purchases. With changing lifestyles and increasing income, consumers are increasingly eating out of home (Akbay et al, 2007;Scozzafava et al, 2017;Leschewski et al, 2018). Future studies should therefore examine similarities, differences as well as interactions between food consumption at home and out of home to analyse the healthfulness of the households' overall diet.…”
Section: Discussionmentioning
confidence: 99%